Determinants of depressive mood in coronary artery disease patients with obstructive sleep apnea and response to continuous positive airway pressure treatment in non-sleepy and sleepy phenotypes in the RICCADSA cohort - BALCAN, MEHMET BARAN (WILEY, 2019)
We explored determinants of depressive mood in adults with coronary artery disease and obstructive sleep apnea and response to positive airway pressure treatment in sleepy and non-sleepy phenotypes. In this secondary analysis of the RICCADSA trial conducted in Sweden, 493 cardiac patients with obstructive sleep apnea (n = 386) or no obstructive sleep apnea (n = 107) with complete Epworth Sleepiness Scale and Zung Self-rating Depression Scale questionnaires were included. Sleepy (Epworth Sleepiness Scale >= 10) versus non-sleepy (Epworth Sleepiness Scale <10) patients with depressive mood (Zung Self-rating Depression Scale score >= 50) were evaluated after 3 and 12 months of positive airway pressure treatment. In all, 133 patients (27.0%) had depressive mood (29.3% of obstructive sleep apnea versus 18.7% of no obstructive sleep apnea; p = 0.029), with a higher percentage among the sleepy phenotype (36.9% versus 24.5%; p = 0.009). In multivariate analysis, depressive mood was significantly associated with female sex, body mass index and Epworth Sleepiness Scale. Among 97 obstructive sleep apnea patients with depressive mood at baseline, there was a significant reduction in the scores at follow-up both in the sleepy and non-sleepy patients allocated to positive airway pressure treatment, whereas no significant changes were observed in the untreated group (p = 0.033). The device use (hr/night) predicted improvement in mood (odds ratio, 1.33; 95% confidence interval, 1.10-1.61; p = 0.003) adjusted for age, female sex, body mass index, left ventricular ejection fraction, apnea-hypopnea index and delta Epworth Sleepiness Scale score. We conclude that obstructive sleep apnea was associated with depressive mood in adults with coronary artery disease. Treatment with positive airway pressure improved mood in both phenotypes, independent of the confounding factors.
Keywords: coronary artery disease; daytime sleepiness; depression; obstructive sleep apnea; positive airway pressure; QUALITY-OF-LIFE; MYOCARDIAL-INFARCTION; DAYTIME SLEEPINESS; TRAFFIC ACCIDENTS; SYMPTOMS; CPAP; MORTALITY; RISK; POPULATION; EFFICACY